Analysis decorating design on Perahu Buatan Barat, the Malay traditional boat by using frieze pattern - Abdul Wahab, Mohd Rohaizat; Ramli, Zuliskandar; Ahmad Zakaria, Ros Mahwati; Abdul Samad, Mohammad Anis (AIP Publishing, 2016)
Boat building tradition is one of the skills mastered by Malay craftsmen. Decoration on the Perahu Buatan Barat, the Malay traditional boat is one of the uniqueness of the production of traditional boats in East Coast of Malaysia. The tradition of Malay boat building, each plank was given specific names based on the line of planks. There is one line called ‘papan tarik’ or ‘papan cantik’ was usually decorated with paintings by a variety of motifs and patterns from the bow to the stern of the boat. The motifs usually taken from the surrounding environment as well as flora and fauna will be painted with motifs repeated but with differing formations. The aim of this study is to identify the motifs and analyze the formation of motifs by using mathematical methods of frieze pattern.